2009
DOI: 10.1088/0031-9155/54/14/n03
|View full text |Cite
|
Sign up to set email alerts
|

The photo-electric current in laser-Doppler flowmetry by Monte Carlo simulations

Abstract: Monte Carlo (MC) simulations significantly contributed to a better understanding of laser-Doppler flowmetry (LDF). Here it is shown that the data obtained from standard MC simulations can be reinterpreted and used to extract more information such as the photo-electric current (i(t)). This is important because i(t) is the starting point for evaluating any existing or new algorithm to be used in LDF instrumentation. This circumvents the tedious procedure of generating a specific model (often approximated if poss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 52 publications
0
11
0
Order By: Relevance
“…As reported in section 3, the 'noise-like' component of i(t) is an intrinsic property of LDF measurements and requires us to average N avg moments to obtain a reliable result. As already explained elsewhere (Binzoni et al 2009), the presence of this 'noise-like' component is due to the random phase accumulated by the photons before reaching the detector. This is a pure physical phenomenon generated by the interaction between the biological tissue and the photons.…”
Section: The Maximum Speed Limit Of a Real-time Ldfmentioning
confidence: 75%
See 1 more Smart Citation
“…As reported in section 3, the 'noise-like' component of i(t) is an intrinsic property of LDF measurements and requires us to average N avg moments to obtain a reliable result. As already explained elsewhere (Binzoni et al 2009), the presence of this 'noise-like' component is due to the random phase accumulated by the photons before reaching the detector. This is a pure physical phenomenon generated by the interaction between the biological tissue and the photons.…”
Section: The Maximum Speed Limit Of a Real-time Ldfmentioning
confidence: 75%
“…From each simulation, 100 different i(t) realizations taking into account the possible random phase accumulated by the photons along their travel inside the tissue were obtained (Binzoni et al 2009). Intuitively, the random phase manifests itself as the noise-like appearance of i(t) and explains also why it is experimentally necessary to average many power spectra (obtained from different i(t)) to obtain one noise-free spectrum (in the present case we have the choice to average from 1 up to 100 spectra); the chosen number of averages is denoted by N avg .…”
Section: Monte Carlo Simulation Of I(t)mentioning
confidence: 99%
“…The reason for that was attributed to the physical characteristics of the phantom used (Fredriksson et al, 2006). A recent study (Binzoni et al, 2009) suggested a reinterpretation of the Monte Carlo simulation in order to obtain more information, relevant to LDF measurements. The authors suggested a method for photo-electric current determination in Monte Carlo simulations which will allow that any algorithm used in real LDF instrument could be tested and validated.…”
Section: Monte Carlo Simulations Applied To the Microcirculation Domainmentioning
confidence: 99%
“…The surface of the tissue was then scanned with a laser beam, thus generating an image of the spatial variability of blood perfusion. Another method, using a CMOS matrix, was proposed by Serov et al, with a view to accelerating the imaging procedure [6].…”
Section: Introductionmentioning
confidence: 99%